Clinical and biochemical profile of hyponatremia and the role of vaptans in comparison to other standard modalities of therapy - Ahmed, Jalal; Khan, Mohammed Fahad; Umakanth, Shashikiran; Shetty, Seema (International Journal of Research in Medical Sciences, 2023)
Background: This study, conducted from August 2014 to August 2015, investigated hyponatremia in 228 in-hospital patients, aiming to discern its clinical and biochemical features and compare the efficacy of vaptans against standard treatments. The null hypothesis assumed no significant disparity in outcomes, while the alternate hypothesis posited otherwise. Methods: Using an open-label, non-blinded, observational, prospective comparative design, we assessed 228 hyponatremia patients. We scrutinized their clinical and biochemical profiles and made comparisons between moderate and profound hyponatremia cases, along with different treatment approaches. Results: Our findings revealed that patients aged 61-80, primarily females, dominated the cohort. Moderate hyponatremia occurred in 56.6% of cases, with severe hyponatremia in 43.4%. Common symptoms included drowsiness, nausea, and vomiting. Euvolemic hyponatremia was predominantly due to SIADH, while heart failure led to most hypervolemic cases. Various treatments were employed, with fluid restriction and normal saline being common. Tolvaptan and 1.6% hypertonic saline significantly increased serum sodium levels at 24 and 48 hours. Hospital stay duration didn’t significantly differ, and no osmotic demyelination cases emerged. Mortality stood at 10.5%, notably higher in profound hyponatremia cases. Conclusions: This study provides insights into hyponatremia’s clinical and biochemical aspects and compares vaptans to standard treatments. Tolvaptan and hypertonic saline displayed promise in raising serum sodium levels. Nevertheless, further research is warranted to validate these findings and explore additional factors impacting hyponatremia treatment outcomes.